Micronutrient status of dairy cattle in new alluvial zone of West Bengal - DAS, P; BISWAS, S; GHOSH, T K; HALDAR, S (The Indian Journal of Animal Sciences, 2014)
A survey on soil-plant-animal relationship in the new alluvial zone of West Bengal indicated that 41.67% of the surveyed farmers kept their animals on grazing and paddy straw supplementation, while 21.16% of them offered their animals with either rice bran or mustard-cake. Coqientrations of Ca, P, Cu, Zn, and Fe in the commonly used feeds and fodder were within the normal range of variation;Â  Mean plasma concentration of Ca, P, Cu, Zn and Fe were within the respective critical ranges in calves, heifers, milch animals as well as in dry ones; however, anestrous animals had shown somewhat lower plasma Ca, P and Cu concentrations. Higher plasma values were observed for Cu and Fe in high yielders. The study bolstered the importance of supplementation of the metabolically important mineral elements.